2002
DOI: 10.1177/009145090202900405
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholics Anonymous Discourse and Members' Resistance in a Virtual Community: Exploring Tensions between Theory and Practice

Abstract: Alcoholics Anonymous has greatly informed the individual, social, and political landscape of the contemporary self-help or mutual-aid movement. There has emerged, in turn, a vast, though largely uncritical, body of research examining AA and its 12-step recovery model. A close look inside a virtual AA community, however, reveals that not all AA members embrace formal AA discourse. Through an examination of dialogue and discourse on a public Usenet newsgroup, this study demonstrates that in contrast to research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Interpretative Phenomenological Analysis (IPA) of people in long-term AA recovery has found that participants tended to knowingly use the AA programme to help them in their pursuit of self-formation towards various ethical ideals (Medina, 2014;Shinebourne and Smith, 2011). Foucauldian studies involving actual members of AA found that AA discourse was drawn on pragmatically and often in ways that, far from reflecting indoctrination, reflected agency in the subversion of core AA tenets (Kitchin, 2002;Valverde and White-Mair, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Interpretative Phenomenological Analysis (IPA) of people in long-term AA recovery has found that participants tended to knowingly use the AA programme to help them in their pursuit of self-formation towards various ethical ideals (Medina, 2014;Shinebourne and Smith, 2011). Foucauldian studies involving actual members of AA found that AA discourse was drawn on pragmatically and often in ways that, far from reflecting indoctrination, reflected agency in the subversion of core AA tenets (Kitchin, 2002;Valverde and White-Mair, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although AA originated in the United States in an overtly religious sociohistorical context, it is found equally effective when practiced in less religious populations (Gossop et al, 2005), but researchers have suggested it may work through a different mechanism within less religious cultures (Kelly et al, 2011). Both AA and Step by Step enable people to become helpers, but in AA, the spiritual component of the vision that enables becoming a helper (Kelly et al, 2011) is also reported to be stigma barrier (Kitchin, 2002). The Step by Step emphasis on internal control is less easily misconstrued, and practical support replaces spirituality.…”
Section: Overcoming Stigma and Giving Practical Support Facilitate Emmentioning
confidence: 99%
“…AA focuses on the control of alcoholism as a disease (Wright, 1997 Kitchin, 2002;VanLear, Sheehan, Withers, & Walker, 2005). Participants are encouraged to admit their alcoholism, find a sponsor in the group, and work through specific steps toward sobriety (Davison, Pennebaker, & Dickerson, 2000).…”
Section: Alcoholics Anonymous (Aa)mentioning
confidence: 99%